Chaos and cosmos. Preliminary notes for a critique of public order - Saporiti , Michele (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
Public order is a central and complex notion. This essay tries to provide the basic elements for a general theoretical critique of such a category, that is deeply employed in political and legal thought. In such a perspective, the analysis is divided into five different parts: the ontology, the physics, the politics, theethics, and the esthetics of public order. The working mechanisms and the presuppositions of each part are carefully scrutinised.
Keywords: public order; ontology; physics; politics; ethics; esthetics; general theory